Design of rectangular patched microstrip antenna at 2300 MHz - Siva Reddy, B; V.R.Vittal, M; ThillaiThilagam.J, Salai (International Journal of Engineering and Technology, 2018)
This research paper explains the design of rectangular shaped patch microstrip antenna power fed with coaxial probe feed, which is working around 2300 MHz 4G LTE band of frequency. It is designed by using the FR4 substrate. It applies to the devices which work around this frequency. Theoretical calculations are made and simulation results are performed using Zeland IE3D Software. Their simulation of antenna results exhibits the gain of 1.5 dB, return loss of -14 dB, VSWR of 1.5 and bandwidth of 80 MHz.Â Â